Pengembangan Handout Kimia Berbasis Chemoenterprenurship pada Materi Larutan Penyangga, Hidrolisis Garam dan Koloid untuk SMA Kelas XI - Afifah Deswita (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
ABSTRACT Research is based on existing problems, namely the lack of availability of practical tools and materials at school so that the practicum is carried out less than the maximum and also the lack of availability of teaching materials for practicum the. The purpose of this research is to make students understand the learning material through the practicum carried out, which is related to directly with everyday life and produce practical handouts chemoenterpreneurship-based chemistry on buffer solution materials, hydrolysis salt and colloid for SMA class XI. This research uses the type of development research with using a development model that is 4-D which consists of 4 stages, namely, define (definition), design (design), develop (development) and disseminate (spread). However, this research is only limited to the third. The results showed that the validation of chemical handouts based on chemoenterpreneurship on buffer solution materials, salt hydrolysis and class XI colloids that have been designed to be valid obtain an average percentage of 75% and the practical results are very practical, obtaining an average percentage of 85% There are two practicalities, namely the practicality of teachers and students. With this can concluded that the designed practicall handout is valid and can be used in the practical implementation process.Keywords: Handout, Chemoenterpreneurship